Politics meets healthcare? Religious misinformation in India during the COVID-19 pandemic - Md. Sayeed Al-Zaman (Jurnal Sosial Humaniora, 2020)
India has recently become a hotspot of misinformation: the COVID-19 bringsa new opportunity for the rumor-spreaders. Of various categories, religiousmisinformation seems harmful for both Indian society and public health. Inthis paper, therefore, I tried to sketch a few necessary aspects of religiousmisinformation in India during the COVID-19. From the previous literatureand ongoing trend of Indian misinformation, I identified two importantphenomena: (a) Though Muslims produce more spiritual misinformation,most of the religious misinformation targeting Muslims is inspired byIslamophobia; (b) misinformation that tries to champion Hinduism is morerelated to the contemporary political ideologies of India. I also tried to explainhow religion as a political issue relates to public health